'Common criminals, simple justice': The social construction of crime in nineteenth century Ontario, 1840-1881. - McLean, Lorna R. (University of Ottawa (Canada), 1996)
During the course of the nineteenth century as recently settled communities solidified, expanded and developed the nature of crime and criminal law altered in substantial ways. The thesis analyzes this process by selecting four communities at different stages of development to explore the basis for such diversity through an examination of gaol registers and case files. Investigating other sources confirmed that these differences were not only economically based but reflected a fundamental shift in ideological thinking. Overall, the evolving process of social development from a frontier/agricultural community to an urban/industrial society affected the nature and social functioning of criminal justice in surprisingly different ways. For example we consider vagrancy, the major public peace offence in rural areas, we observe that it served as a surrogate for social welfare until the end of the nineteenth century. In contrast, in urban areas patterns of prosecution and punishment for the most common crime, drunkenness, reflected the combined influences of reform movements, expansion of local municipal by-laws and police enforcement that accompanied urbanization. Together the combined impact of regulatory policies with gendered ideologies resulted in more women than men committed for public peace offences in Toronto/York between 1855 and 1865 than at any other time in the later nineteenth century. In addition, one constant that united all communities was how masculine culture contributed to both the violent disputes which erupted in public between men and the private assaults that husbands inflicted on wives. A further exploration of violence in rural areas revealed how networks of economic interdependence among family, friends and neighbours alongside practices of traditional frontier culture could, on occasion, lead to violent conflicts. Overall, the evidence indicates that frontier and rural areas fostered a greater degree of violence than in the cities. However, across all communities, the law reflected a certain ambivalence towards wife-beating in the home, with the courts reluctant, at times, to convict or pass severe penalties to limit domestic patriarchal controls. Local variations also existed among property offences. In rural areas theft often served to resolve personal disputes over ownership as neighbors and business acquaintances resorted to stealing capital goods to resolve private financial disputes. In urban areas theft generally involved individuals who stole personal goods from employers, underscoring the widening economic divisions between classes. In their occupational roles as prostitutes and servants, women comprised a large cross section of the individuals charged with theft. Overall in rural areas instances of grand larceny were charged as "petty" and under differing circumstances in urban areas petty larceny was treated as "grand." Overwhelmingly in both urban and rural communities it seems that those who laid the charges were from a higher position in the social hierarchy and in urban areas those charged were largely working class. A comparative study of criminals and crime informs us not only of the evolving nature of criminal justice, it also delineates how the particular social and economic stage of a community influences other broad social factors including the development and social meaning of crime and the criminal law. Exploring this interactive process among individuals, communities and the state assists in identifying some of the fundamental principles governing society.
Keywords: History, Canadian.